Neutrophil Extracellular Traps (NETs) in Sterile Inflammatory Diseases - Ji YM; Li T; Qin YH; Xiao SY; Lv YH; Dong Y; Cui XR; Hu Y (Journal of Inflammation Research)
Yin-Min Ji,1– 3,* Tao Li,1,3– 5,* Yu-Hui Qin,1,3,* Shu-Yan Xiao,1,3 Ya-Hui Lv,1,3 Yi Dong,1,3 Xiao-Ran Cui,1,3,6 Yi Hu1,3,6 1Senior Department of Oncology, the First Medical Center of PLA General Hospital, Beijing, 100853, People’s Republic of China; 2Department of Oncology, the Second Affiliated Hospital of Anhui Medical University, Hefei, 230601, People’s Republic of China; 3Medical School of Chinese PLA, Beijing, 100853, People’s Republic of China; 4Department of Stomatology, the First Medical Center of PLA General Hospital, Beijing, 100853, People’s Republic of China; 5Changchun Veterinary Research Institute, Chinese Academy of Agricultural Sciences, Key Laboratory of Jilin Province for Zoonosis Prevention and Control, Changchun, Jilin, 130122, People’s Republic of China; 6Senior Department of Oncology, the Fifth Medical Center; Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiao-Ran Cui, Email cooboozhi@gmail.com Yi Hu, Email huyi301zlxb@sina.comAbstract: Neutrophil Extracellular Traps (NETs) are fibrous web-like structures released by neutrophils in response to pathogenic infections or inflammatory stimuli. Composed of decondensed chromatin DNA, histones, and granular proteins, NETs primarily function to eliminate pathogens through physical entrapment and biochemical cytotoxicity. However, they may also contribute to the pathogenesis of inflammatory diseases. While NETs played an important role in pathogen defense, their non-specific components can also damage surrounding tissues, exacerbating inflammation. The role and mechanisms of NETs in various diseases have been well-documented, including autoimmune diseases, cancer, and infectious diseases. This review aims to elaborate on the mechanisms by which NETs mediate sterile inflammation.Keywords: neutrophils, extracellular traps, autoimmune diseases, sterile inflammation, immune checkpoint inhibitors, ICIs